HIDRORENGKAH MINYAK LAKA MENGGUNAKAN KATALIS NiO/ZEOLIT ALAM AKTIF DAN NiOMoO/ZEOLIT ALAM AKTIF MENJADI FRAKSI BERPOTENSI ENERGI - Darma Santi; Lisna Efiyanti (BRIN Publishing, 2014)
Hydrocracking of cashew-nut shell liquid (CNSL) into energy-affording fractions has been investigated using catalyst of acid-actiated natural zeolite (ZAA), to which were further impregnated unimetal (NiO) and bimetal (NiOMo) elements, thereby comprising two catalyst types (NiO/ZAA and NiOMoO/ZAA). This research aimed to examine how potential was the conversion of CNSL into energy-affording fractions, and to look into such metal impregnation into ZAA catalyst on the performance of hydrocracking reaction. Catalyst characterization included determining consecutively acidity using ammonia-base adsorption, and crystallinity using X-ray diffraction (XRD). Acid activation and metal impregnation increased the catalyst acidity and its crystallinity. The hydrocracking was carried out in a fixed-bed reactor employing the temperature 450°C, the CNSL feed/catalyst ratio of 6, and flow rate of H₂ at 20 ml/minute. The hydrocracking converted the CNSL into products that comprised the liquid-phase, gas-phase, and solid-phase (cokes) fractions, which in all afforded energy, and the conversion of each was examined. The liquid-phase product was further analyzed using gas chromatography (GC), which revealed that the GC's eluted liquid fraction were predominantly gasoline, diesel oil, and heavy oil. Each eluted fraction was further examined for its selectivity based on the elucidated GC area for each fraction over the total GC area for the overall liquid fractions. The hydrocracking performed optimally using NiOMo/ZAA catalysts. Which converted as much 75.42% (the greatest) of the CNSL as the liquid product, with also the greatest in selectivity towards gasoline and diesel-oil fraction at 38.45% and 19.87%, respectively. The impregnation of metal element, particularly bimetal (NiOMo) into ZAA catalyst indicatively enhanced the hydrocracking performance.